2019
DOI: 10.1002/mrd.23306
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic compounds within the porcine uterine environment are unique to the type of conceptus present during the early stages of blastocyst elongation

Abstract: The objective of this study was to identify metabolites within the porcine uterine milieu during the early stages of blastocyst elongation. At Days 9, 10, or 11 of gestation, reproductive tracts of White cross-bred gilts (n = 38) were collected immediately following harvest and flushed with Roswell Park Memorial Institute-1640 medium. Conceptus morphologies were assessed from each pregnancy and corresponding uterine flushings were assigned to one of five treatment groups based on these morphologies: (a) unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…In the current study, several genes involved in phospholipid and glycerophospholipid metabolism (Figure 5b ) (Kumari et al, 2012 ; Prasad et al, 2011 ; Shulga et al, 2011 ; C. L. E. Yen et al, 2002 ), phosphatidylcholine and phosphatidylethanolamine metabolism (Figure 5c ) (Cao et al, 2008 ; Golczak et al, 2012 ; Horibata & Hirabayashi, 2007 ; Payton et al, 2004 ; Schaloske & Dennis, 2006 ; Tsuboi et al, 2015 ), and the metabolism of membrane sphingolipids (Figure 5d ) (T. J. Kim et al, 2006 ; Lahiri et al, 2007 ; Tafesse et al, 2007 ; Takahashi & Suzuki, 2012 ; Xu et al, 2006 ) were significantly differentially expressed between 1st MT conceptus stages and T versus S morphologies. Previous studies have observed an increase in proteins involved in the metabolism of ceramide and other membrane sphingolipids, as well as in glycerophospholipid and sphingolipid metabolites, within uterine luminal fluid at the time of porcine conceptus elongation (Kayser et al, 2006 ; Walsh et al, 2020 ), providing further support for involvement of phospholipid membrane compositional changes in the initiation of porcine conceptus elongation. In addition to regulating cell maintenance and growth, membrane phospholipids play important roles in regulating membrane−associated protein activities and serve as precursors of bioactive lipids involved in intracellular signaling (Cao et al, 2008 ; Shulga et al, 2011 ; Tafesse et al, 2007 ; Takahashi & Suzuki, 2012 ).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In the current study, several genes involved in phospholipid and glycerophospholipid metabolism (Figure 5b ) (Kumari et al, 2012 ; Prasad et al, 2011 ; Shulga et al, 2011 ; C. L. E. Yen et al, 2002 ), phosphatidylcholine and phosphatidylethanolamine metabolism (Figure 5c ) (Cao et al, 2008 ; Golczak et al, 2012 ; Horibata & Hirabayashi, 2007 ; Payton et al, 2004 ; Schaloske & Dennis, 2006 ; Tsuboi et al, 2015 ), and the metabolism of membrane sphingolipids (Figure 5d ) (T. J. Kim et al, 2006 ; Lahiri et al, 2007 ; Tafesse et al, 2007 ; Takahashi & Suzuki, 2012 ; Xu et al, 2006 ) were significantly differentially expressed between 1st MT conceptus stages and T versus S morphologies. Previous studies have observed an increase in proteins involved in the metabolism of ceramide and other membrane sphingolipids, as well as in glycerophospholipid and sphingolipid metabolites, within uterine luminal fluid at the time of porcine conceptus elongation (Kayser et al, 2006 ; Walsh et al, 2020 ), providing further support for involvement of phospholipid membrane compositional changes in the initiation of porcine conceptus elongation. In addition to regulating cell maintenance and growth, membrane phospholipids play important roles in regulating membrane−associated protein activities and serve as precursors of bioactive lipids involved in intracellular signaling (Cao et al, 2008 ; Shulga et al, 2011 ; Tafesse et al, 2007 ; Takahashi & Suzuki, 2012 ).…”
Section: Discussionmentioning
confidence: 72%
“…Kim et al, 2006;Lahiri et al, 2007;Tafesse et al, 2007;Takahashi & Suzuki, 2012;Xu et al, 2006) were significantly differentially expressed between 1st MT conceptus stages and T versus S morphologies. Previous studies have observed an increase in proteins involved in the metabolism of ceramide and other membrane sphingolipids, as well as in glycerophospholipid and sphingolipid metabolites, within uterine luminal fluid at the time of porcine conceptus elongation (Kayser et al, 2006;Walsh et al, 2020), providing further support for involvement of phospholipid membrane compositional changes in the initiation of porcine conceptus elongation. In addition to regulating cell maintenance and growth, membrane phospholipids play important roles in regulating membrane−associated protein activities and serve as precursors of bioactive lipids involved in intracellular signaling (Cao et al, 2008;Shulga et al, 2011;Tafesse et al, 2007;Takahashi & Suzuki, 2012).…”
Section: Phospholipid Membrane Remodeling and Lipid Signalingmentioning
confidence: 62%
“…As such, the scarcity of comprehensive in vivo data (66,67) render robust comparisons a challenge. Rectifying this is by thoroughly metabolically profiling uterine fluid from women, similarly to what has been conducted in cattle (63,(68)(69)(70), sheep (71), pigs (72), and mice (73) will shed much needed light on the biochemistry surrounding maternal-embryo communication in our species, and allow us to better evaluate the merits of IOF as a UF surrogate.…”
Section: Discussionmentioning
confidence: 99%
“…After thorough mixing, 100 μL were aliquoted, dried under nitrogen, and then stored until analysis. The analysis of the dried samples was carried out at -80˚C as per Walsh et al [34]. Briefly, the dried samples were resuspended in 50 μL of pyridine containing 25 mg/mL of methoxyamine hydrochloride and incubated at 60˚C for 45 min.…”
Section: Analysis Of Leaf Petiole and Stem Exudatesmentioning
confidence: 99%